2018
DOI: 10.5114/fmpcr.2018.73702
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and reliability testing of the SHARE-FI instrument for the assessment of risk of frailty syndrome among older Polish patients

Abstract: Background. Frailty reduces independence, quality of life and psychological well-being. Frailty also increases the risk of geriatric syndromes, addictions, hospitalization, institutionalization, disability and mortality in the oldest population of every society. Objectives. the main aim of this research was the adaptation and validation of the sHare-Fi questionnaire, identifying the risk of frailty syndrome in a group of people over 60 years of age in Poland. another aim was to create Polish calculators for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The results of this study showed that the Polish version of SHARE-FI has high internal consistency and reliability coefficients and can be recommended for screening among 60+ older adults in primary care and hospital settings. In the study, Cronbach’s alpha coefficient was 0.79 19…”
Section: Methodsmentioning
confidence: 86%
“…The results of this study showed that the Polish version of SHARE-FI has high internal consistency and reliability coefficients and can be recommended for screening among 60+ older adults in primary care and hospital settings. In the study, Cronbach’s alpha coefficient was 0.79 19…”
Section: Methodsmentioning
confidence: 86%
“…Frailty syndrome was assessed using the Frailty Instrument of the Survey of Health, Aging and Retirement in Europe (SHARE-FI), which is recommended as a screening test in primary health care and hospital care in people over 60 years of age of both sexes ( 3 , 21 ). Translation and validation procedure of the Polish version of the SHARE-FI was completed by Muszalik ( 22 ). The questions included in the SHARE-FI concern the following areas: the subject's gender, subjective feeling of exhaustion, loss of appetite, difficulty in walking upstairs, reduction in physical activity, and assessment of handgrip strength (measured with a manual hydraulic dynamometer SAEHAN SH501) ( 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Translation and validation procedure of the Polish version of the SHARE-FI was completed by Muszalik ( 22 ). The questions included in the SHARE-FI concern the following areas: the subject's gender, subjective feeling of exhaustion, loss of appetite, difficulty in walking upstairs, reduction in physical activity, and assessment of handgrip strength (measured with a manual hydraulic dynamometer SAEHAN SH501) ( 22 , 23 ). The obtained numerical values calculated with the use of the SHARE-FI virtual calculator allow the subject to be classified into one of the three groups: non-frail, pre-frail and frail ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Frailty syndrome was assessed using the Survey of Health, Aging, and Retirement in Europe SHARE-FI, which is recommended as a screening test in primary health care and hospital care in people over 60 years of age of both sexes [ 5 ]. The translation and validation procedure of the Polish version of the SHARE-FI was completed by M. Muszalik et al The results of Cronbach’s alpha reliability coefficients of the SHARE-FI instrument ranged from 0.73 to 0.83, and the corrected item-total correlation ranged from 0.11 to 0.91 [ 35 ]. The questions included in the SHARE-FI concern the following areas: the subject’s gender, subjective feeling of exhaustion, loss of appetite, difficulty in walking upstairs, limitation in physical activity, and assessment of handgrip strength (measured with a manual hydraulic dynamometer SAEHAN SH501).…”
Section: Methodsmentioning
confidence: 99%